COMBINATION EFFECT OF NITROGEN LASER ANDCHLOROHEXIDINE ON THE VIABILITY OF Pseudomonas aeruginosa - Anwer, Ayad (Iraqi Journal of Science, 2024)
To evaluate the Combination effect of Nitrogen laser and chlorohexidine on the viability of Pseudomonas aeruginosa that isolated from burns, the samples of bacteria were irradiated with 337.1 nm Nitrogen laser using 5 and 10 pulses/second repetition rates , at 1 , 5, 10 ,15, 25 minutes exposure times . The irradiation was done with and without treatment with chlorohexidine respectively. The results showed that there is a noticeable effect of Laser on the viability of bacteria with the presence of chlorohexidine. The viability of bacteria decreased with increasing the exposure time and pulse repetition rate.